Women and COVID-19 in Gauteng - Parker, Alexandra; Maree, Gillian; Götz, Graeme; Khanyile, Samkelisiwe (Gauteng City-Region Obervatory, 2020)
This August 2020 Map of the Month is presented as a story map and draws on the infection data from the Gauteng Department of Health (6 March - 7 August 2020) and GCRO’s March 2020 COVID-19 vulnerability indices based on Quality of Life V (2017/18) survey data, to understand the ways in which women may be more vulnerable than men to COVID-19. We also explore some of the implications for this gender bias in the number of positive cases.
This August 2020 Map of the Month is presented as a story map and draws on the infection data from the Gauteng Department of Health (6 March - 7 August 2020) and GCRO’s March 2020 COVID-19 vulnerability indices based on Quality of Life V (2017/18) survey data, to understand the ways in which women may be more vulnerable than men to COVID-19. We also explore some of the implications for this gender bias in the number of positive cases.